A testament to the greatness of traditional marine technology: an introduction to Perahu Besar Terengganu - Nor Suraya Aini Ngah; Ramly Hasan; Nor Syamaliah Ngah; Tengku Azman Tengku Mohd; Che Muhamad Azmi Ngah; Inche Mokhtar Awang; Mohd Yusof Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2025)
The settlement of the Japanese in Malaysia has had several impacts, including on Malay heritage, particularly the endangered maritime heritage Perahu Besar Terengganu. Currently, only two units of Perahu Besar Terengganu are left, underscoring the urgent need to preserve this significant Malay heritage. Perahu Besar Terengganu played crucial roles not just in commerce but also in international relations, serving as a mode of transportation for people and festivals during times of war. This study aims to shed light on the different types of Perahu Besar Terengganu and their evolution. Aligned to achieve Sustainable Development Goal (SDG) 11, this study seeks to support the SDG 17 by fostering collaboration among several institutions including the Ministry of Higher Education, Universiti Malaysia Kelantan, Universiti Teknologi Mara Seremban, Politeknik Ungku Omar, Terengganu State Museum, and the Royal Terengganu Institute for Historical and Legal Studies. The methodology used is a qualitative approach. Data was collected through document reviews and in-depth interviews, involving historians and experienced boatbuilders from Kuala Terengganu. The study has revealed four types of Perahu Besar Terengganu which is Perahu Besar Dogol, Perahu Besar Anak Bedar, Perahu Besar Pinis Dogol and Perahu Besar Pinis Gobel. The evolution of these four types of Perahu Besar originated with Perahu Besar Dogol. The type of Perahu Besar is identified based on the unique characteristics of its stern and hull shape. Despite variations in aesthetics, the functions and other components of these Perahu Besar Terengganu remain consistent. These differences reflect the embodiment of human wisdom, external influences, and the creative skills of the boatbuilders. The recommendation of this study is to explore the specific components of Perahu Besar Terengganu, which will contribute further to our understanding of this remarkable heritage.